Sourcing from China: Connecting Inward and Outward Internationalisation Through Absorptive Capacity - ANUAR, NUR IZZATI MOHAMAD; ZAINOL, NOOR RAIHANI; HASHIM, NIK ALIF AMRI NIK; ZULKIFFLI, WAN FARHA WAN; ZAINUDDIN, SITI AFIQAH; REDZUAN, RAZMAN HAFIFI; ABDULLAH, TAHIRAH (The journal of contemporary issues in business and government, 2021)
The capabilities of small and medium enterprises (SMEs) to partake in the global value chain (GVC) are remarkable. However, the capabilities of SMEs to connect between the sourcing side of GVC to the export side of GVC through learning processes should also be addressed for the SMEs’ competitive gains. Therefore, the objective of this study is to investigate firm’s absorptive capacity in connecting their inward to outward internationalisation by employing a qualitative case study design using two cases involving Malaysian SMEs’ internationalisation as well as semi-structured interviews with the SMEs’ Managing Directors for two years, and the data were then triangulated through documentation. Based on the research findings, the absorptive capacity of SMEs should be equipped with inter-firm knowledge sharing and “guanxi” relationship in order to utilize the newly acquired knowledge by means of a reciprocal action and trust involving the focal firm and their suppliers in China. This enables SMEs to benefit from the flows of knowledge in inward and outward internationalisation, thus able to export to China even though they only began from international sourcing.